Food materials science and engineering - Bhandari, Bhesh (Wiley-Blackwell, 2012)
"Food Materials Science and Engineering covers a comprehensive range of topics in relation to food materials, their properties and characterisation techniques, thus offering a new approach to understanding food production and quality control"--